Aetiology and prevention of injuries in elite young athletes - Maffulli, N.; Longo, U. G.; Spiezia, F.; Denaro, V. (The Elite young athlete, 2011)
Sport participation confers many varied benefits in children and adolescents, such as self-esteem, confidence, team play, fitness, agility and strength. Nevertheless, the age of initiation of intense training is decreasing and programmes which expose children to excessive amounts of exercise increase the risk of injury. We review sports injuries in young athletes and the long-term outcomes. Sports injuries can lead to disturbances in growth such as limb length discrepancy, caused by traumatised physeal growth induced by injury. Osgood-Schlatter lesion may also cause some sequelae such as painful ossicles in the distal patellar tendon. The apophysis can be fragmentised or separated, and this could be an adaptive change to the increased stress typical of overuse activities. These changes produce an osseous reaction even though they are not disabling. Participation in physical exercise at a young age should be encouraged, because of the health benefits, but decreasing the incidence and severity of sports injuries in young athletes is an important component of any athletic programme and may generate a long-term economic impact in health care costs. Active prevention measures are the main weapon to decrease the (re-)injury rate and to increase athletic performance.